ANALISIS PENGARUH PENGALAMAN KERJA, DISIPLIN KERJA, DAN PENGEMBANGAN SDM TERHADAP KINERJA (Studi Pada Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kendal) - Maulana, Afiz; Rozak, Hasan Abdul (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to determine the effect of human resource development, work experience, and work discipline on performance at the Public Works and Spatial Planning Office of Kendal Regency. By using a census approach, the study population was 52 civil servants in the personnel department. The data collection method used in this study was a questionnaire that used quantitative data types. The data testing techniques used were validity test, reliability test, multiple linear regression test, T test, F test, and determination coefficient test (R2) with SPSS 29 software. The results showed that: Performance is not significantly influenced by work experience partially. Performance is positively and significantly influenced by work discipline. Performance is positively and significantly influenced by human resource development. Performance is positively and significantly influenced by work experience, and work discipline, human resource development simultaneously. Keywords : Work Experience, Work Discipline, Human Resource Development, Performance